The Human Rights Turn and the Paradox of Progress in the Middle East - Hosseinioun, Mishana (Middle East Today, 2018)
This book aims to shift the limited and often negative popular understanding of the Middle East's place in the world by chronicling the region's contributions to the international order rather than disorder, and to the development of the international human rights system. It elucidates the many paradoxes that make the Middle East and North Africa (MENA) region both a troubling place and also a region brimming with great potential for peace, prosperity and progress. By demonstrating the paradox of human rights progress amid regress, the book tells a radically new and more hopeful side of the story of the region that has largely been obfuscated and omitted from the chronicles of history. In so doing, it shows that fostering a human rights culture is not only possible for all universally, it is inevitable. .